Challenges and Opportunities in Accessing Subsidized Home Ownership Credit for Informal Sector Workers (Case Study at Bank Tabungan Negara, Bitung City) - Caerol Runtu, Tonny Chrishard; Kumenaung, Anderson G.; Rorong, Ita Pingkan (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the challenges and opportunities for informal sector workers in accessing subsidized mortgages (KPR) in Bitung City, focusing on Bank Tabungan Negara (BTN). The research method used was a qualitative approach. The results indicate that the main obstacles faced by informal sector workers include income instability, limited official documents, and strict banking regulations. However, opportunities exist through financing innovation, the role of fintech, and government financial inclusion policies. Based on these findings, the study recommends more flexible policies and the use of financial technology to increase the accessibility of subsidized mortgages for informal sector workers.